Blood global DNA methylation is decreased in non-severe chronic obstructive pulmonary disease (COPD) patients. (October 2017) - Zinellu, Angelo; Sotgiu, Elisabetta; Fois, Alessandro G.; Zinellu, Elisabetta; Sotgia, Salvatore; Ena, Sara; Mangoni, Arduino A.; Carru, Ciriaco; Pirina, Pietro
Abstract: Background: Alterations in global DNA methylation have been associated with oxidative stress (OS). Since chronic obstructive pulmonary disease (COPD) is characterized by increased oxidative stress we aimed to evaluate the levels of global DNA methylation in this patient group. Methods: We assessed methylcytosine (mCyt) levels in DNA from blood collected in 43 COPD patients (29 with mild and 14 with moderate disease) and 43 age- and sex-matched healthy controls. Results: DNA methylation was significantly lower in COPD patients vs. controls (4.20 ± 0.18% mCyt vs. 4.29 ± 0.18% mCyt, p = 0.02). Furthermore, DNA methylation in COPD patients with moderate disease was significantly lower than that in patients with mild disease (4.14 ± 0.15% mCyt vs. 4.23 ± 0.19% mCyt, p < 0.05). Univariate logistic regression analysis showed that lower DNA methylation levels were associated with presence of COPD (crude OR = 0.06, 95% CI 0.00 to 0.67, p = 0.023). This relationship remained significant after adjusting for several confounders (OR 0.03, 95% CI 0.00 to 0.67; p = 0.028). Receiver operating characteristics (ROC) curve analysis demonstrated the area under the curve of mCyt was 0.646, with 46.6% sensitivity and 79.1% specificity for presence of COPD. Conclusions: There were no significant correlations between methylation and OS indices. The presence and severity of COPD is associated with progressively lower DNA methylation in blood. However, this epigenetic alteration seems independent of oxidative stress.